Proteomic Identification of Rhythmic Proteins in Maize Seedling Leaves - Wan-jun FENG; Bao-jian GUO; Ying-ym YAO; Hui-ru PENG; Qi-xin SUN; Zhong-fu NI (Journal of Integrative Agriculture, 2012)
Plant leaves respond to day/night cycling in a number of physiological ways. At the mRNA level, the expression of some genes changes during the 24 h period. To determine which proteins exhibited a rhythmic pattern of expression, proteomic profiles in maize seedling leaves were analyzed by high-throughput two-dimensional gel electrophoresis, combined with MALDI-TOF MS technology. Of the 464 proteins that were detected with silver staining in a pH range of 4-7, 17 (3.66%) showed clock rhythmicity in their abundance. These proteins belonged to diverse functional groups and proteins involved in photosynthesis and carbon metabolism were over-represented. These findings provide a new perspective on the relationship between the physiological functions of leaves and the clock rhythmic system.